2010
DOI: 10.1186/1742-2094-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 18 in the CNS

Abstract: Interleukin (IL)-18 is a cytokine isolated as an important modulator of immune responses and subsequently shown to be pleiotropic. IL-18 and its receptors are expressed in the central nervous system (CNS) where they participate in neuroinflammatory/neurodegenerative processes but also influence homeostasis and behavior. Work on IL-18 null mice, the localization of the IL-18 receptor complex in neurons and the neuronal expression of decoy isoforms of the receptor subunits are beginning to reveal the complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
201
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(212 citation statements)
references
References 165 publications
(182 reference statements)
7
201
0
4
Order By: Relevance
“…Additionally, prolonged allograft ischemic time has been associated with impaired gas exchange (i.e., Pa O 2 /FI O 2 ) immediately postoperatively (34) and impaired longterm survival. Confirmatory studies, designed to examine markers of oxidative stress (34,35), inflammation (e.g., IL-18) (35,(43)(44)(45), and oxygenation postoperatively as potential mediators of the observed relationships between allograft ischemic time, oxygenation, and cognitive function, are required to validate our observations. Related future studies are required to examine whether the previously identified relationship between prolonged allograft ischemic time and long-term survival (34) is mediated by cognitive impairment and the potential adverse events related to such impairment (i.e., functional impairment, medication nonadherence, infectious complications) (46,47).…”
Section: Original Researchmentioning
confidence: 86%
“…Additionally, prolonged allograft ischemic time has been associated with impaired gas exchange (i.e., Pa O 2 /FI O 2 ) immediately postoperatively (34) and impaired longterm survival. Confirmatory studies, designed to examine markers of oxidative stress (34,35), inflammation (e.g., IL-18) (35,(43)(44)(45), and oxygenation postoperatively as potential mediators of the observed relationships between allograft ischemic time, oxygenation, and cognitive function, are required to validate our observations. Related future studies are required to examine whether the previously identified relationship between prolonged allograft ischemic time and long-term survival (34) is mediated by cognitive impairment and the potential adverse events related to such impairment (i.e., functional impairment, medication nonadherence, infectious complications) (46,47).…”
Section: Original Researchmentioning
confidence: 86%
“…In contrast, IL-18 was originally identified as an interferon-␥-inducing factor, and can enhance the production of other inflammatory molecules such as IL-1␤, tumor necrosis factor-␣, and the inducible form of nitric oxide synthase. 25 The precise pathway between inflammation process and SVD is largely unknown and needs additional investigation. Our results have some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…После секреции он связывается либо с ИЛ-18-рецепторным антагонистом, инактивирующим его, либо с комплексом, состоящим из рецептора ИЛ-1R5 и ИЛ-18-дополняющего белка (ИЛ-1R7). После формирования лиганд-рецепторного соединения к нему прикрепля-ются цитозольные белки MyD88 (myeloid differentiation primary response gene 88) и IRAK-1 (interleukin-1 receptorassociated kinase 1), активирующие транскрипционный фактор NF-κB [3,10]. Активация ИЛ-18 может приводить к усилению цикла ИФН-γ/ИЛ-18: ИЛ-18 индуцирует образование лимфоцитами ИФН-γ, который стимулирует моноциты/макрофаги с увеличением их ICE-активности, что способствует синтезу ИЛ-18 [8].…”
Section: особенности строения и активации членов семейства ил-1unclassified
“…Иммуносупрессивное воздействие избытка глюкокортикоидов сопровождается снижением числа циркулирующих в крови Т-и В-лимфоцитов, моно-цитов, эозинофилов и базофилов, ограничением способ-ности макрофагов к фагоцитозу и киллингу злокаче-ственно трансформированных клеток [11]. Установлено, что ИЛ-18 способен угнетать нейроэндокринную деятель-ность, проявляя антагонизм по отношению к эффектам ИЛ-1β [10,18].…”
Section: биологические свойства цитокинов семейства ил-1unclassified